IDENTIFIKASI FRAGMEN DNA MIOGLOBIN SEPANJANG 114PB PADA BEBERAPA JENIS HEWAN LAUT YANG MAMPU HIDUP PADA ZONA MINIMUM OKSIGEN - Febrianti, Isrina; Puspitaningrum, Rini; Rusdi, Rusdi (LPPM Universitas Negeri Jakarta, 2015)
ABSTRACT Myoglobin is a hemoprotein that contributes to intracellular oxygen storage and facilitates diffusion oxygen into mitochondria. Myoglobin production will increase as low levels of environmental oxygen called hypoxia. When oxygen in tissue is low, the body will respond by forming myoglobin in some tissues, such as muscle tissue. The aims of this study was to detect DNA fragments of myoglobin along 114pb in muscle tissue of marine animals are capable to live in the oxygen minimum zone, such as the green turtle, mackerel tuna and hammerhead sharks. The oxygen minimum zone is zone of oceans which have low dissolved oxygen levels at > 1,4Î¼LO2L-1, the oxygen levels can be categorized as hypoxic conditions. This study was conducted in the Biochemistry laboratory, State University of Jakarta. This study used descriptive method by PCR and electrophoresis. The results indicated that myoglobin found in muscles of marine animals were capable live in oxygen minimum zone such as the green turtle, mackerel tuna and hammerhead shark. This information can be used as the basic that the tissue able to make adaptation strategy towards low oxygen environmental levels by increasing formation of myoglobin in muscle tissue. Kata kunci: Myoglobin DNA, Green Turtle, Mackerel Tuna and Hammerhead Sharks